Tempo de atividade física total e fatores sociodemográficos na população brasileira : pesquisa nacional de saúde 2019 - Santos, Izabella Cristina da Silva (2023)
Purpose: to analyze the association between Total Physical Activity and Sociodemographic Factors in Brazilians. Methods: Cross-sectional study with secondary data from the 2019´s National Health Survey - Brazil. It was considered as sample all subjects over 18 years of age who composed the database, totaling 91,683 subjects of both genders. Quantile regression was used to verify the possible associations between the variables, considering the 0.25, 0.50, and 0.75 percentiles as cutoff points. Results: For the sociodemographic variables considered in the study, it was observed that adults have a longer time of practice of Total Physical Activity than the elderly in all quantiles considered. The variables "Color/Ethnicity" and "Schooling" indicated association from Q50, and for "Color/Ethnicity" the self-declared "whites" obtained a lower volume of total physical activity. Considering schooling, it was found that the group that indicated “not knowing how to read” accumulates lower results of Total Physical Activity, when compared to literates. Conclusion: the associations coincided with characteristics of less affluent groups, but attention should be paid to the importance of studying the lower amounts of Total Physical Activity, favoring the interventions for this group.